Changes in mRNA expression precede changes in microRNA expression in lesional psoriatic skin during treatment with adalimumab. (14th July 2015) - Raaby, L.; Langkilde, A.; Kjellerup, R.B.; Vinter, H.; Khatib, S.H.; Hjuler, K.F.; Johansen, C.; Iversen, L.
Abstract : What's already known about this topic? MicroRNAs (miRNAs) are known regulators of mRNA expression and miRNA expression is altered in psoriatic skin. Tumour necrosis factor (TNF)‐α inhibitors are effective treatments for psoriasis and changes in cytokine expression profile occur in the skin after a few days of treatment. What does this study add? This study showed no change in miRNA expression after 4 days of adalimumab treatment indicating that the early cytokine changes seen in psoriatic skin during treatment are not facilitated by changes in miRNA expression. The changes in miRNA expression seen 14 days after treatment initiation is more likely a result of the improvement of the disease than of anti‐TNF‐α itself, as limited regulation was seen in the TNF‐α KO mouse. Summary: Background: Tumour necrosis factor (TNF)‐α inhibition is an effective treatment for moderate to severe plaque‐type psoriasis. A change in the cytokine expression profile occurs in the skin after 4 days of treatment, preceding any clinical or histological improvements. MicroRNAs (miRNAs) are important post‐transcriptional regulators of gene expression, but miRNA expression has never been studied in psoriatic skin during treatment. Objective: To investigate changes in miRNA expression in psoriatic skin during adalimumab treatment and to compare results with changes in miRNA expression in a mouse model of Aldara‐induced psoriasis‐like skin inflammation. Methods: Punch biopsies were obtained from nonlesional and lesional psoriatic skin during adalimumab treatment. In the mouse model of Aldara‐induced skin inflammation, biopsies were obtained from TNF‐α knockout (KO), IL‐17A KO and wild‐type mice. miRNA expression levels were analysed with microarray, reverse transcriptase quantitative polymerase chain reaction and in situ hybridization. Results: In psoriatic skin, no changes in miRNA expression were seen 4 days after treatment initiation. After 14 days of treatment, the expression of several miRNAs was normalized towards the level seen in nonlesional skin before treatment. miR‐23b expression increased after 14 days of treatment and remained high for 84 days, despite unaltered levels at baseline. In the mouse model of Aldara‐induced skin inflammation, the level of miR‐146a increased, whereas no regulation was seen for miR‐203, miR‐214‐3p, miR‐125a, miR‐23b or let‐7d‐5p. Conclusions: This study demonstrates that the changes seen in the cytokine expression levels after 4 days of treatment with adalimumab are not facilitated by early changes in miRNA expression.